Down into the nether - Davidson, Danica (Davidson, Danica. Unofficial Overworld adventure, 2016)
"The prophecies on music discs suggest that only Stevie and Alex, plus Maison, Destiny and Yancy, their friends from the human world will be able to defeat Herobrine. But the prophecies also warn that one of the friends will betray the rest, putting all the worlds at risk. Tensions run high as the group must figure out how to save the world while they try to discern the traitor in their midst. Maison, It isn't long before the traitor is discovered"--